2012
DOI: 10.1107/s174430911203103x
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic characterization of mouse AIM2 HIN-200 domain bound to a 15 bp and an 18 bp double-stranded DNA

Abstract: AIM2 (absent in melanoma 2) is an innate immune receptor for cytosolic double-stranded DNA (dsDNA). The engagement of dsDNA by AIM2 activates the AIM2 inflammasome, resulting in the cleavage of pro-interleukin-1 by caspase-1. The DNA-binding HIN-200 domain of mouse AIM2 bound to a 15 bp dsDNA and to an 18 bp dsDNA was purified and crystallized. The AIM2 HIN-200 domain in complex with the 15 bp DNA crystallized in the cubic space group I23 or I2 1 3, with unit-cell parameter a = 235.60 Å . The complex of the AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Structural studies of the AIM2 inflammasome have so far been focused on its HIN domain (34,58). Based on the electro- static nature of the AIM2 HIN domain association with dsDNA, we hypothesized that an intramolecular interaction between the HIN domain and PYD retains the receptor in an autoinhibited state in the absence of ligand binding (34).…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies of the AIM2 inflammasome have so far been focused on its HIN domain (34,58). Based on the electro- static nature of the AIM2 HIN domain association with dsDNA, we hypothesized that an intramolecular interaction between the HIN domain and PYD retains the receptor in an autoinhibited state in the absence of ligand binding (34).…”
Section: Discussionmentioning
confidence: 99%
“…ALRs were described to bind dsDNA of virtually any origin including microbial, host or synthetic molecules that vary in sequence and GC content . The lack of apparent specificity of the HIN‐DNA interactions is supported by the nature of the HIN‐DNA interactions . Sensitivity of HIN‐DNA interaction to ionic strength suggested the involvement of electrostatic attractions .…”
Section: Aim2 Detection Of Dnamentioning
confidence: 99%
“…Sensitivity of HIN‐DNA interaction to ionic strength suggested the involvement of electrostatic attractions . Moreover, crystallographic analyses of DNA interaction with AIM2 and IFI16 revealed that the hydrophobic pocket of the HIN binds both strands of DNA on the sugar‐phosphate backbone across major and minor grooves . In the absence of DNA ALRs are in an autoinhibited state with PYD and HIN domains.…”
Section: Aim2 Detection Of Dnamentioning
confidence: 99%
“…Structural studies of AIM2, IFI16, and p202 show that the two OB folds are rigidly linked via a connecting α-helix and almost orthogonal to each other (9497) (Figure 5 a ). AIM2 and IFI16 HIN domains interact with classical B-form dsDNA in a similar manner, using mostly electrostatic contacts between the highly charged surface of HIN domains and backbone phosphates of dsDNA (94, 96).…”
Section: The Aim2-like Receptor and Nod-like Receptor Inflammasomesmentioning
confidence: 99%